Pembangunan Huntara sebagai Bentuk Respon Pemerintah terhadap Bencana Tanah Gerak di Desa Sambirejo Tahun 2024 - Dhian Satria Yudha Kartika; Tina Adelia Lestari; Nashrum Minallah; Isma Triana; Gracia Medyate Sinulingga; Inayah Divia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A disaster is an event that can occur due to several factors and can claim lives. Indonesia is a country that has the potential for natural disasters because it is traversed by three plates. Jumok Hamlet in Sambirejo Village just experienced a landslide disaster in early 2023 which destroyed 13 houses. Land movement in Sambirejo Village can occur because the village is located on the slopes of the foot of a mountain and is surrounded by hills. This caused the Government to build and provide temporary shelter for affected victims. Apart from shelters, the government also provides household equipment for consumption throughout the fasting month. Exactly in March 2024, Group 8 students from UPNVJT carried out KKNT-MBKM in Sambirejo Village. Group 8 students were involved and worked directly with the BPBD and other institutions to provide this assistance and prepare for the HUNTARA. This article aims to provide a description of the Government's response to the disaster that occurred, providing an overview of the formation of the Huntara, and the role of group 8 who happened to be carrying out KKNT-MBKM at that time.